Mineralogy and Rock Response Analysis Approach to Mitigate Wellbore Stability issue in â€œBâ€ Cluster of East Java Field - Andi Andi Andi (Journal of Petroleum and Geothermal Technology, 2023)
The instability of shales in drilled formations leads to serious operational problems with major economic consequences for petroleum exploration and production. It is generally has agreed that the nature of the clay minerals in shale formations is a primary causative factor leading to their instability, although the exact mechanism involved is more debatable. Currently, the principal cause of shale instability is considered to be volume expansion following the osmotic swelling of sodium smectite. However, illitic and Kaolinite shales may also be unstable, so that interlayer expansion cannot therefore be consider as a universal causative mechanism of shale instability. This review considers alternative scenarios of shale instability where the major clay minerals Kaolinite suspected to be a key success to mitigate the wellbore stability. It is found from the literature that the inhibited by the use of more concentrated Potassium-based fluids which is effectively shrink the thickness of the clay mineral surfaces in the pore walls but may differently responded by Kaolinite dominant clay. The use of soluble polymers would also encapsulate these clay mineral surfaces and so inhibit their hydration. In this scenario, the locus of action with respect to shale instability and its inhibition is moved from the interlamellar space of the smectitic clays to the charged external surfaces of the various clay minerals bounding the walls of the shale pores.Â Keywords: shale instability, smectitic shale, illitic shale, Kaolinitic shale.